Cloning and analysis of s-triazine catabolic genes from Pseudomonas sp. strain NRRLB-12227. - Eaton, R W (1991)
Pseudomonas sp. strain NRRLB-12227 degrades the s-triazine melamine by a six-step pathway which allows it to use melamine and pathway intermediates as nitrogen sources. With the plasmid pLG221, mutants defective in five of the six steps of the pathway were generated. Tn5-containing-EcoRI fragments from these mutants were cloned and identified by selection for Tn5-encoded kanamycin resistance in transformants. A restriction fragment from ammelide-negative mutant RE411 was used as a probe in colony hybridization experiments to identify cloned wild-type s-triazine catabolic genes encoding ammeline aminohydrolase, ammelide aminohydrolase, and cyanuric acid amidohydrolase. These genes were cloned from total cellular DNA on several similar, but not identical, HindIII fragments, as well as on a PstI fragment and a BglII fragment. Restriction mapping and Southern hybridization analyses of these cloned DNA fragments suggested that these s-triazine catabolic genes may be located on a transposable element, the ends of which are identical 2.2-kb insertion sequences.